Interaction of human osteoblast-like Saos-2 and MG-63 cells with thermally oxidized surfaces of a titanium-niobium alloy - Vandrovcova, Marta; Jirka, Ivan; Novotna, Katarina; Lisa, Vera; Frank, Otakar; Kolska, Zdenka; Stary, Vladimir; Bacakova, Lucie (PLoS One, 2014)
An investigation was made of the adhesion, growth and differentiation of osteoblast-like MG-63 and Saos-2 cells on titanium (Ti) and niobium (Nb) supports and on TiNb alloy with surfaces oxidized at 165°C under hydrothermal conditions and at 600°C in a stream of air. The oxidation mode and the chemical composition of the samples tuned the morphology, topography and distribution of the charge on their surfaces, which enabled us to evaluate the importance of these material characteristics in the interaction of the cells with the sample surface. Numbers of adhered MG-63 and Saos-2 cells correlated with the number of positively-charged (related with the Nb2O5 phase) and negatively-charged sites (related with the TiO2 phase) on the alloy surface. Proliferation of these cells is correlated with the presence of positively-charged (i.e. basic) sites of the Nb2O5 alloy phase, while cell differentiation is correlated with negatively-charged (acidic) sites of the TiO2 alloy phase. The number of charged sites and adhered cells was substantially higher on the alloy sample oxidized at 600°C than on the hydrothermally treated sample at 165°C. The expression values of osteoblast differentiation markers (collagen type I and osteocalcin) were higher for cells grown on the Ti samples than for those grown on the TiNb samples. This was more particularly apparent in the samples treated at 165°C. No considerable immune activation of murine macrophage-like RAW 264.7 cells on the tested samples was found. The secretion of TNF-α by these cells into the cell culture media was much lower than for either cells grown in the presence of bacterial lipopolysaccharide, or untreated control samples. Thus, oxidized Ti and TiNb are both promising materials for bone implantation; TiNb for applications where bone cell proliferation is desirable, and Ti for induction of osteogenic cell differentiation.
Keywords: Animals; kolagen typu I; proliferace buněk; tkáňové podpůrné struktury; buněčné linie; lipopolysacharidy; biologické markery; vysoká teplota; Biomarkers; makrofágy; Tumor Necrosis Factor-alpha; osteoblasty; statická elektřina; povrchové vlastnosti; Hot Temperature; buněčná adheze; buněčná diferenciace; lidé; osteokalcin; Macrophages; Mice; Cell Adhesion; Osteocalcin; Lipopolysaccharides; myši; slitiny; Cell Line; oxidace-redukce; TNF-alfa; Osteoblasts; Oxidation-Reduction; Alloys; Cell Proliferation; Cell Differentiation; zvířata; Collagen Type I; Tissue Scaffolds; Surface Properties; Static Electricity; Humans